2023
DOI: 10.1139/cjm-2022-0092
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum BW2013 protects mucosal integrity and modulates gut microbiota of mice with colitis

Abstract: This study explored the effects of L. plantarum BW2013 on mucosal integrity and gut microbiota of mice with dextran sulphate sodium (DSS) induced colitis. The results show that the clinical symptoms in DSS modelled ulcerative colitis (UC) were improved by L. plantarum BW2013 via decreasing disease activity index (DAI) scores and suppressing inflammatory cell infiltration. Furthermore, L. plantarum BW2013 decreased the levels of diamine oxidase (DAO) activity, myeloperoxidase (MPO) and D-lactic acid (DLA). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Moreover, Odoribacter and Lachnospiraceae_NK4A136_group reportedly promote the production of butyric acid, which plays an important role in maintaining the internal pH of the gut and protecting intestinal health 45,46 . Rikenella , a beneficial bacterium, has an inhibitory effect on inflammation 47 . Clinical studies have found a higher abundance of Ruminococcus in the gut of patients with inflammatory bowel diseases compared to healthy populations 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Odoribacter and Lachnospiraceae_NK4A136_group reportedly promote the production of butyric acid, which plays an important role in maintaining the internal pH of the gut and protecting intestinal health 45,46 . Rikenella , a beneficial bacterium, has an inhibitory effect on inflammation 47 . Clinical studies have found a higher abundance of Ruminococcus in the gut of patients with inflammatory bowel diseases compared to healthy populations 48 .…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Rikenella, a beneficial bacterium, has an inhibitory effect on inflammation. 47 Clinical studies have found a higher abundance of Ruminococcus in the gut of patients with inflammatory bowel diseases compared to healthy populations. 48 Furthermore, Desulfovibrio is a pathogenic bacterium that can cause bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…However, disadvantages of this treatment include high recurrence rates and low remission rates (Chen et al, 2022). Previous studies showed that probiotic intervention can effectively regulate intestinal inflammation and reduce the damage (Niu et al, 2023;Sharma et al, 2023). Therefore, probiotics have become an alternative for preventing and treating several diseases, such as enteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, probiotics have become an alternative for preventing and treating several diseases, such as enteritis. In addition, the DSS-induced mouse enteritis model is easy to operate and has been applied to many probiotics in evaluating the effects on colitis such as Lactobacillus plantarum, Bifidobacterium and so on (Niu et al, 2023;Wang et al, 2023). Consequently, a DSS-induced mouse enteritis model was used to study the effect of C. butyricum isolated from giant panda feces.…”
Section: Discussionmentioning
confidence: 99%
“…(Di Cagno et al., 2019). LP BW2013 alleviated dextran sodium sulfate (DSS)‐modeled UC by protecting mucosal integrity and ameliorating the composition of gut microbiota (Niu et al., 2023). LB treatment attenuated the clinical signs of intestinal inflammation, reducing the intestinal and tumor levels of IL‐6, TNF‐α, IL‐17, IL‐23, and IL‐1 beta (Calheiros Silveira et al., 2020).…”
Section: Introductionmentioning
confidence: 99%